Integrating Machine Learning Algorithms with Cybersecurity Observability Frameworks for Real-Time Threat Detection and Automated Incident Response (Journal of Artificial Intelligence Research, 2023)
This paper explores the integration of machine learning algorithms within cybersecurity observability frameworks to enhance real-time threat detection and automated incident response. As cyber threats become increasingly sophisticated, traditional security measures are no longer sufficient to guarantee robust defense mechanisms. By leveraging the power of machine learning, specifically anomaly detection models, supervised and unsupervised learning techniques, and predictive analytics, the observability of network traffic and system logs can be significantly improved. This integration allows for the identification of previously unknown or evolving threats that might otherwise go undetected by conventional rule-based systems. The research delves into how machine learning models, when applied to large-scale security data, can facilitate the automatic detection of anomalies and the prediction of potential vulnerabilities before they escalate into critical security breaches. Additionally, the paper examines deployment strategies within hybrid cloud environments, where the fusion of machine learning and observability tools can provide proactive security measures, ensuring continuous monitoring and quick response to incidents. The challenges of implementing these models at scale, ensuring minimal false positives, and addressing privacy concerns are also discussed. This paper ultimately aims to demonstrate that integrating machine learning with observability frameworks is a vital step toward achieving a more dynamic, responsive, and secure cybersecurity landscape.
Keywords: machine learning; cybersecurity; observability; anomaly detection